The RanGTP Pathway: From Nucleo-Cytoplasmic Transport to Spindle Assembly and Beyond - Cavazza, Tommaso; Vernos, Isabelle (Frontiers in Cell and Developmental Biology, 2016)
The small GTPase Ran regulates the interaction of transport receptors with a number of cellular cargo proteins. The high affinity binding of the GTP-bound form of Ran to import receptors promotes cargo release, whereas its binding to export receptors stabilizes their interaction with the cargo. This basic mechanism linked to the asymmetric distribution of the two nucleotide-bound forms of Ran between the nucleus and the cytoplasm generates a switch like mechanism controlling nucleo-cytoplasmic transport. Since 1999, we have known that after nuclear envelope breakdown (NEBD) Ran and the above transport receptors also provide a local control over the activity of factors driving spindle assembly and regulating other aspects of cell division. The identification and functional characterization of RanGTP mitotic targets is providing novel insights into mechanisms essential for cell division. Here we review our current knowledge on the RanGTP system and its regulation and we focus on the recent advances made through the characterization of its mitotic targets. We then briefly review the novel functions of the pathway that were recently described. Altogether, the RanGTP system has moonlighting functions exerting a spatial control over protein interactions that drive specific functions depending on the cellular context.